Revisiting harmful algal blooms in India through a global lens: An integrated framework for enhanced research and monitoring - Aditya R. Nayak; Srinivas Kolluru; Aloke Kumar; Punyasloke Bhadury (iScience)
Summary: Harmful algal bloom (HAB) events substantially impact human and aquatic ecosystem health and the global blue economy; hence, a concerted effort is required to advance our understanding of HAB ecology to better inform monitoring and mitigation measures. Here, we highlight the current state of HAB research and monitoring in India, where ∼17% of the human population resides in the vicinity of its long coastline and is dependent on the sustainable blue economy. Through the lens of established programs from countries across the globe, we identify existing gaps and highlight four broad areas for focusing future efforts: (1) the development/employment of novel technologies for HAB research and monitoring; (2) the need for integrated observation networks and a coordinated effort across different central/state agencies and research institutes; (3) clinical studies on human health effects; and (4) public outreach and citizen science initiatives to increase awareness on this topic, including policy level interventions.